2022
DOI: 10.3390/foods11020203
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Preference and Consumption of Healthy Food in Children

Abstract: According to recent findings, action is urgently needed to promote healthy eating habits among children, especially to increase daily consumption of fresh fruits and vegetables [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Possible scores range from 0 to 60, and higher scores indicate poorer mental health. In addition, prolonged use of screen-media devices has been described as a significant contributor to poor eating patterns in children and adolescents [ 1 , 62 ], so a dummy variable was added to the equation to measure whether students play online games.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible scores range from 0 to 60, and higher scores indicate poorer mental health. In addition, prolonged use of screen-media devices has been described as a significant contributor to poor eating patterns in children and adolescents [ 1 , 62 ], so a dummy variable was added to the equation to measure whether students play online games.…”
Section: Methodsmentioning
confidence: 99%
“…Food preferences, particularly in children, play a pivotal role in predicting human food choices [ 1 ]. Existing studies have shown that only a few taste preferences are innate, and most food preferences are learned through experience with food in social environments during childhood [ 2 ], meaning that food preferences can be modified and changed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to note that poor eating habits are becoming more actual and problematic among consumers (Wagner et al, 2017). These habits are reflected in higher propensities to consume sweets and fatty foods and reduced intake fruits and vegetables (Laureati, 2022). Eating habits regarding rational and healthy eating are also affected by the age of consumers.…”
Section: Attitudes Toward Healthymentioning
confidence: 99%
“…This issue is getting more and more attention because it contributes to various problems and long-term effects and affects a child's life until adulthood if it is not curbed from the beginning. In total, 149 million children under five years of age suffer from stunting (Global Nutrition Report, 2020;Laureati, 2022). In 2020, it was found that the total number of children suffering from stunting was 149.2 million (Petermann-Rocha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%